2017
DOI: 10.11604/pamj.2017.27.255.11378
|View full text |Cite
|
Sign up to set email alerts
|

Social and cultural barriers to husbands� involvement in maternal health in rural, Gambia

Abstract: IntroductionWhile many studies have documented a number of socio-cultural barriers to male involvement in maternal health, in The Gambia very little information is known about the social and cultural practices that characterized male involvement in maternal health. This study aims to explore some of the underlying social and cultural factors affecting husbands’ involvement in maternal health issues pertaining to pregnancy and delivery in rural Gambia.MethodsFive focus group discussions and six in-depth intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 17 publications
7
41
0
1
Order By: Relevance
“…The need for male involvement in reproductive health was one of the fore-front agenda during the International Conference on Population and Development (UNFPA, 1999). Male involvement is highly desirable in maternal health (Lowe, 2017). Because male attendance during ANC is an important strategies to reduce preventable maternal problems during pregnancy (Jennings et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The need for male involvement in reproductive health was one of the fore-front agenda during the International Conference on Population and Development (UNFPA, 1999). Male involvement is highly desirable in maternal health (Lowe, 2017). Because male attendance during ANC is an important strategies to reduce preventable maternal problems during pregnancy (Jennings et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other barriers were also assessed such as the attitude of health care workers, religion and culture but majority of the women did not perceive this as a barrier to male involvement. This therefore shows an improvement in the barriers to male involvement over the years as studies carried out by Iliyasu et al (2010), NPC snd ICF (2013) and Lowe (2017) revealed that attitude of spouses toward husband's participation in maternal care is strongly opposed to the physical presence of husbands in the labour room during delivery due to the strong cultural and religious effects, especially for Muslims. It was however, noted that Christians were more inclined to spousal participation in antenatal and post-natal care (Umeora et al, 2011 as cited in Vehvilainen-Julkunen and Emelonye, 2014).…”
Section: Enabling Factors and Perceived Barriers Towards Male Involvementioning
confidence: 70%
“…Other factors found to hinder the actualization of this desire for males to be involved in labour include education, which has been shown in some studies as a determining factor, reporting high participation of educated men in supporting their wives during antenatal and delivery sessions than uneducated men (Vehvilainen-Julkunen and Emelonye, 2014). Other factors such as ignorance, poverty, cultural and religious practices were shown to be reasons for low spousal participation during delivery (Lowe, 2017). In Nigeria where culture and religion governs the practices of the society, there is a strong cultural belief in several parts of the country that spousal presence worsens labour pain and prolongs labour (National Population Comission, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In El Salvador, women from extended families were less likely to report on male partners' attendance than women from nuclear families (33). In a qualitative study from Gambia, some men who had more than one wife reported that they did not attend childbirth for fear of instilling jealousy among their co-wives (94).…”
Section: Family Structure Influencementioning
confidence: 99%
“…Studies from Gambia, Syria, Botswana, Malawi, Kenya, South Africa, Nigeria, and Rwanda reported that men and women in rural and semi-urban areas did not favour male partners' presence at labour and/or birth. This may have been influenced by cultural norms that regarded pregnancy and childbirth as a woman's realm and patriarchal attitudes that childbirth is an intimate event which a man should not witness (20,22,26,62,70,74,83,91,93,94). In one survey conducted in a rural Rwandan hospital, 51% of women (n=178) said that men's presence at childbirth was not culturally appropriate (37).…”
Section: Sociocultural Barriersmentioning
confidence: 99%